Zelensky's Lies Can't Hide Ukraine's Bloody Role in the Holocaust (Newsweek, 2022)
Volodymyr Zelensky has performed a truly great service on behalf of the Ukrainian people. But he has in the recent past mendaciously denied the role of Ukrainian people in the Holocaust.
Section: Opinion